“The Role of State Madrasah Principals in Improving the Quality of Learning at Madrasah Tsanawiyah in Indonesia - Mubin, Holikul; Irfani, Vivi Putri; Salsabila, Naila Faizah (Ma'arif Journal of Education, Madrasah Innovation and Aswaja Studies, 2025)
This study intends to analiyze and identify the role of prinscipals in Madrasah Tsanawiyah Negeri (MTsN) in Indonesia. The reseach is significant in providing insights for school principals and polymakers to determine appropriate strategies for improving the quality of education. A qualitative reseach method with a systematic literature review approach was employed, with data collected through an analysis of 19 articles relevant to the role of principals in Madrasah Tsanawiyah Negeri in Indonesia. The findings reveal that the principal’s roles as a motivator, innovator, manager, and supervisor positively enhance education quality, despite certain challenges and obstacles. School principals need to strengthen school-based management and academic supervision to improve the quality of learning at Madrasah Tsanawiyah Negeri in Indonesia